A dynamic mutational landscape associated with an inter‐regionally diverse immune response in malignant rhabdoid tumour. Issue 1 (22nd July 2020) - Yasui, Hiroaki; Valind, Anders; Karlsson, Jenny; Pietras, Christina; Jansson, Caroline; Wille, Joakim; Romerius, Patrik; Backman, Torbjörn; Gisselsson, David
Abstract: Malignant rhabdoid tumour (MRT) is a childhood neoplasm of high malignancy characterised by biallelic mutation and/or loss of the epigenetic master regulator SMARCB1, accompanied by no or few other oncogenic drivers. In spite of their generally low mutational burden, an intratumoural T‐cell response has been reported in a subset of MRTs, indicating that immune checkpoint inhibition may be considered a viable therapy option for some patients. We assess here the evolution over time and space of predicted neoantigens and indicators of immune checkpoint status in two MRT patients who progressed under treatment. Both patients showed an accumulation of novel clonal and subclonal mutations, including predicted neoantigens, in metastases compared to their inferred ancestral clones in the primary tumours. The first patient had peritoneal metastases from an MRT of the liver. Clonal deconvolution revealed polyclonal seeding from the primary tumour to a single metastatic site, followed by a local subclonal burst of mutations. The second patient had a renal MRT with multiple pulmonary metastases, each of which could be traced back to a single genetically unique founder cell, with formation of novel subclones in two metastases. Both patients showed a regionally heterogeneous landscape of predicted neoantigens and of tumour‐infiltrating lymphocytes expressing CD8 and PD1. In both patients, some tumour regions fulfilled established criteria for PD‐L1 positivity (> 1% of tumour cells), while others did not. This suggests that even in a tumour type like MRT, with a single driver mutation, there can be heterogeneity in neoantigen repertoire, immune response, and biomarkers for checkpoint blockade among sampled locations. This must be taken into account when assessing progressed MRT patients for checkpoint inhibition therapy. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.